Routine PSA Testing: An Analysis of the Controversy Concerning Its Use - Namath S. Hussain (The Scientific World Journal)
Prostate cancer is the leading cause of cancer in American males today. PSA screening has been used for over 10 years as an important diagnostic tool for the disease. Because of its lack of sensitivity and specificity, however, PSA testing should be used with caution.